Monitoring Kondisi Ruangan Berbasis Iot - Kurniawati Naim; Muhammad Riyan Ardiyansyah (Jurnal Teknologi Elekterika, 2020)
Every person in their daily lives is always connected to the surrounding environment. Environmental conditions will greatly affect every activity that a person does. To get optimal performance, it takes space that supports the activities of the people in it. Room conditions are needed to achieve ideal conditions for activities. Room conditions that are not suitable, especially for storing goods or equipment, can accelerate the damage to equipment or items in the room. This also has an impact if you are leaving the room empty, it will cause your own panic about dangerous things that will occur, for example a fire. To reduce the level of risk that will occur when leaving the room empty, a realtime monitoring system is needed. This journal will discuss the IoT-based room condition monitoring system as a realtime monitoring tool. Monitoring data is transferred to the blynk application server via internet media in a Wi-Fi network. Room conditions including temperature, air humidity, gas levels, fire and smoke predictions are read using sensors and processed using a microcontroller and then displayed through the Blynk application.